Eugenic Ideas and the Foundation of The Institute of Social Medicine - Mendoza de Souza, Walter (1999)
Here we discuss about the influence of eugenic ideas on the foundation and performance of the Faculty of Medicine Institute of Social Medicine (1927). Academic publications from 1910 to 1950, mainly those of Dr. Carlos Enrique Paz Soldan, support our analysis. In the first half of this century, some concepts were developed in the setting of Social Medicine at the Institute. These concepts result in the basis of the emerging public health. Eugenic ideas have arrived beginning the twentieth century, when the policy and intellectual scene of "aristocratic republic" enhanced their development. Social health ideas were appearing, focusing on preventive actions at population-level, in an attempt to avoid Peruvian health impairment and "ethnic degeneration". As a result, several control measures were instaured, giving rise to the need of an institution that was responsible for these measures.